THE CURRENT DEVELOPMENT OF THE TURKISH INSURANCE MARKET ON THE WAY TO EU MEMBERSHIP AND POLICY RECOMMENDATIONS FOR IMPROVEMENT (Third Sector Social Economic Review, 2019)
In the Turkish insurance market, significant developments took place in the 2000s and significant progress was made in developing the market with both the newly established insurance agencies and the new Insurance Law in line with the European Union (EU) legislation. Also in this period, there was a significant revival in the supply and demand for insurance products along with the increase in the share of the insurance market in Turkey from companies with foreign capital. They also contributed to the development of the insurance market in Turkey. Furthermore, the regulations aimed at the insurance market in the context of Turkey's EU candidacy process are also important with regard to the development of the market.In this study, the current structure of the Turkish insurance market on the way to EU membership has been addressed; the development of the insurance market has been statistically determined; policy recommendations have been made with regard to the requirements in order to increase this development.
Keywords: Turkish Insurance Market; Insurance Agengies; Insurance Law; Market Development; Policy Recommendations